2004
DOI: 10.1023/b:neon.0000040811.14908.f2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of N-cadherin expression in high grade gliomas with tissue invasion

Abstract: Cadherins are Ca2+-dependent cell adhesion molecules that play an important role in tissue construction and morphogenesis in multicellular organisms. Over the last few years, reports have emerged in the literature describing the involvement of cadherins in tumor invasion and metastasis. Cadherins typically demonstrate up and down-regulation according to the biological needs of the tissue. Additionally, up-regulation of N-cadherin is thought to be important for tumor formation in early stages of tumor developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 46 publications
12
81
0
Order By: Relevance
“…Changes in N-cadherin expression are still controversial mainly owing to the observation of an inverse correlation between N-cadherin mRNA and protein levels (Asano et al, 2004;Shinoura et al, 1995), which we also observed (data not shown). This discrepancy most probably reflects defects in protein synthesis or stability.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Changes in N-cadherin expression are still controversial mainly owing to the observation of an inverse correlation between N-cadherin mRNA and protein levels (Asano et al, 2004;Shinoura et al, 1995), which we also observed (data not shown). This discrepancy most probably reflects defects in protein synthesis or stability.…”
Section: Discussionsupporting
confidence: 55%
“…Although sometimes contradictory, evidence showing changes in N-cadherin levels in gliomas is accumulating (Asano et al, 2004;Asano et al, 1997;Utsuki et al, 2002). We analyzed N-cadherin levels in normal and glioma samples by western blots.…”
Section: N-cadherin Protein Levels Are Often Downregulated In Glioma mentioning
confidence: 99%
See 1 more Smart Citation
“…cell-cell adhesion ability was detected by an aggregation assay, which was carried out as described previously (15). cells were washed three times with rPMi-1640 (serum-free medium) and were subsequently trypsinized with 4.0 mM eDta with calcium to protect cadherin subtypes on the cell surface from cleavage.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to its role in carcinoma, N-cadherin is frequently downregulated in GBM compared to the healthy brain (177,178). N-cadherin overexpression has been shown to decrease glioma invasion in vitro and in vivo (179). Interestingly, the role of N-cadherin in glioma is postulated not only to be determined by its expression level but also by its distribution in the cell membrane (180).…”
Section: Cadherinsmentioning
confidence: 99%